2018
DOI: 10.20964/2018.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Graphene and Dielectric Property Relationships in PVDF/graphene Nanosheets Composites

Abstract: In this paper, a series of the functionalized graphenes, such as graphene oxide (GO), reduced graphene oxide (rGO), carboxylated graphene oxide (GOCOOH), reduce carboxylated graphene oxide (rGOCOOH), fluorinated graphene oxide (GOF), and reduce fluorinated graphene oxide (rGOF), were successfully fabricated, and were introduced into the Poly (vinylidene fluoride) (PVDF) matrix to form composites. The effects of these functional groups on dielectric properties of GO/PVDF composites were systematically investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…For instance, Zheng et al has demonstrated that incorporation of reduced graphene derivatives exhibit enhanced dielectric permittivity and low dielectric loss as compared to samples without undergoing the reduction reaction. 57 This was attributed to strong interfacial interaction between the PVDF matrix and reduced graphene derivatives. The frequency dependent dielectric constant and dielectric loss of PVDF doped with various graphene derivatives of compression-molded samples are presented in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Zheng et al has demonstrated that incorporation of reduced graphene derivatives exhibit enhanced dielectric permittivity and low dielectric loss as compared to samples without undergoing the reduction reaction. 57 This was attributed to strong interfacial interaction between the PVDF matrix and reduced graphene derivatives. The frequency dependent dielectric constant and dielectric loss of PVDF doped with various graphene derivatives of compression-molded samples are presented in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Methods for achieving the dispersion of graphene in polymer matrices [14] usually include the use of a solvent in which both graphene and the polymer are dispersed and then co-precipitated [15]. Alternatively, the solvent is evaporated, and the dried dispersion is obtained as a film [16,17]. Another method that consists of adding graphene to the monomer before polymerization is carried out to obtain the corresponding composite material [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…711,1821 GOs can be chemically coated onto the surfaces of either carbon fibers or carbon fabric to augment the interfacial bonding properties through the surrounding polymer matrix of the composites. 1217,2227 On the other hand, poly(vinylindene fluoride) (PVDF) is known for displaying ferroelectric behavior below 150 °C while pyroelectric and piezoelectric properties at room temperature. 28,29 It also exhibits low dissipation and good permittivity.…”
Section: Introductionmentioning
confidence: 99%